Perkembangan Bisnis Rumput Laut di Indonesia: Tinjauan Literatur Tentang Tren dan Tantangan (2019-2024) - Nur Hidayat; Nurani Fissilmi Kaaffah; Monica Juniarti Anjvita Situmorang; Erikah Azzahrawani Subekti; Denny Oktavina Radianto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
his study examines the business development of seaweed in Indonesia during the period of 2019-2024 through a comprehensive literature review. Findings indicate substantial growth in the seaweed industry during this period, with promising increases in production and exports contributing significantly to the national economy. However, challenges such as production issues, global competition, and regulatory obstacles are also identified. Strategic measures are needed to optimize the potential of this industry, including improving production quality, market expansion, government collaboration, and human resource development. Close cooperation with relevant stakeholders, including the government and academic institutions, can strengthen the seaweed industry. Supportive policies, investment in research and development, and training programs to enhance workforce skills are key to overcoming the challenges faced by this sector. The findings of this study are expected to provide valuable insights for stakeholders in the seaweed industry and make a meaningful contribution to academic literature on this topic. With the right steps, the seaweed industry in Indonesia has the potential to continue growing sustainably and significantly benefit economic growth and societal welfare.